Mechanically tunable exchange coupling of Co/CoO bilayers on flexible muscovite substrates. Issue 5 (23rd January 2020) - Ha, Thai Duy; Yen, Min; Lai, Yu-Hong; Kuo, Chang-Yang; Chen, Chien-Te; Tanaka, Arata; Tsai, Li-Zai; Zhao, Yi-Feng; Duan, Chun-Gang; Lee, Shang-Fan; Chang, Chun-Fu; Juang, Jenh-Yih; et al.
Abstract : A mechanical bending method was utilized to apply strain to flexible Co/CoO bilayers and control the exchange coupling between the two layers. Abstract : The employment of flexible muscovite substrates has given us the feasibility of applying strain to heterostructures dynamically by mechanical bending. In this study, this novel approach is utilized to investigate strain effects on the exchange coupling in ferromagnetic Co and anti-ferromagnetic CoO (Co/CoO) bilayers. Two different Co/CoO bilayer heterostructures were grown on muscovite substrates by oxide molecular beam epitaxy, with the CoO layer being purely (111)- and (100)-oriented. The strain-dependent exchange coupling effect can only be observed on Co/CoO(100)/mica but not on Co/CoO(111)/mica. The origin of this phenomenon is attributed to the anisotropic spin re-orientation induced by mechanical bending. The strain-dependent magnetic anisotropy of the bilayers determined by anisotropic magnetoresistance measurements confirms this conjecture. This study elucidates the fundamental understanding of how magnetic exchange coupling can be tuned by externally applied strain via mechanical bending and, hence, provides a novel approach for implementing flexible spintronic devices.